Mesial temporal lobe epilepsy – An overview of surgical techniques. (December 2016) - Muzumdar, Dattatraya; Patil, Manoj; Goel, Atul; Ravat, Sangeeta; Sawant, Nina; Shah, Urvashi
Abstract: Mesial temporal lobe epilepsy is one of the commonest indications for epilepsy surgery. Presurgical evaluation for drug resistant epilepsy and identification of appropriate candidates for surgery is essential for optimal seizure freedom. The anatomy of mesial temporal lobe is complex and needs to be understood in the context of the advanced imaging, ictal and interictal Video_EEG monitoring, neuropsychology and psychiatric considerations. The completeness of disconnection of epileptogenic neural networks is paramount and is correlated with the extent of resection of the mesial temporal structures. In the Indian subcontinent, a standard but extended anterior temporal lobectomy is a viable option in view of the diverse socioeconomic, cultural and pathological considerations. The maximum utilization of epilepsy surgery services in this region is also a challenge. There is a need for regional comprehensive epilepsy care teams in a tertiary care academic hospital to form centers of excellence catering to a large population. Highlights: Hippocampal sclerosis is the most common cause of mesial temporal lobe epilepsy. Anterior temporal polar focal cortical dysplasia is often missed on a routine MR protocol. A 3T MR imaging is necessary with an experienced MR radiologist. Diffuse cortical dysplasia and severely sclerotic hippocampus can pose surgical challenge. A Standard but extended anterior temporal lobectomy is appropriate in the Indian subcontinent due to various cultural and socioeconomic considerations. Comprehensive epilepsy care team in a tertiary care academic is paramount for the success of the epilepsy care program.